محددات التدفقات التجارية لدول إتفاق أغادير: نهج نموذج الجاذبية - عاشور, الصادق; حاجي, فطيمة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى التحري عن محددات التدفقات التجارية لدول إتفاق أغادير مع 57 شريكا تجاريا خلال الفترة (2000-2019). أظهرت النتائج عدم تأثر التدفقات التجارية لدول إتفاق أغادير بالتقارب الجغرافي والثقافي، والتأثير البسيط لعدم الاستقرار السياسي. كما يبدو أن إتفاقيات التجارة الحرة، بما فيها إتفاقية أغادير كان تأثيرها أكثر وضوحا على تجارة الدول الأعضاء. أما مؤشر تركز صادرات دول أغادير فلديه قوة تفسيرية كبيرة على التدفقات التجارية. This study aims to investigate the determinants of trade flows in the Agadir agreement countries with 57 trading partners during the period (2000-2019). The results showed that commercial flows to the Agadir countries were not affected by geographical and cultural convergence and the slight effect of political instability. It also appears that FTAs, including the Agadir Agreement, have had a more pronounced impact on the trade of member states. As for Agadir's export concentration index, it has a large explanatory power on trade flows.
Determinants of trade flows to Agadir agreement countries: Gravity Model Approach
مقال
Keywords: نموذج الجاذبية ; بيانات البانل ; إتفاقية أغادير ; إتفاقية تجارة حرة ; مؤشر التركز